Enhancing coastal winds and surface ocean currents with deep learning for short-term wave forecasting - Manuel García-León; José María García-Valdecasas; Lotfi Aouf; Alice Dalphinet; Juan Asensio; Stefania Angela Ciliberti; Breogán Gómez; Víctor Aquino; Roland Aznar; Marcos Sotillo (Ocean Science, 2025)
Accurate short-term wave forecasts are crucial for numerous maritime activities. Wind and surface currents, the primary forcings for spectral wave models, directly influence forecast accuracy. While remote sensing technologies like Satellite Synthetic Aperture Radar (SAR) and High Frequency Radar (HFR) provide high-resolution spatio-temporal data, their integration into operational ocean forecasting remains challenging. This contribution proposes a methodology for improving these operational forcings by correcting them with Artificial Neural Networks (ANNs). These ANNs leverage remote sensing data as targets, learning complex spatial patterns from the existing forcing fields used as predictors. The methodology has been tested at three pilot sites in the Iberian–Biscay–Ireland region: (i) Galicia, (ii) Tarragona and (iii) Gran Canaria. Using SAR as a reference, the ANN corrected winds present Root Mean Square Deviation (RMSD) reductions close to 35 % respect to ECMWF-IFS, and improvements close to 3 % for the scatter-index. Surface currents are also improved with ANNs, reaching speed and directional biases close to 2 cm s−1 and 6° and correlation close to 35 % and 50 %, respectively. Using these ANN forcings in a regional spectral wave model (Copernicus Marine IBI-WAV NRT) leads to improvements in the Wave Height (Hm0) bias and RMSD around 10 % and 5 % at the NE Atlantic. Mean wave period (Tm02) also improves, with reductions of 17 % and 5 % in bias and RMSD. Preliminary moderate improvements were also present in extreme events (e.g. storm Arwen at Galicia, November 2021), as the Hm0 was corrected close to 0.5 m and Tm02 by around 0.4 s. However, properly quantifying this impact requires further assessment.

Evaluation of the Operational CMEMS and Coastal Downstream Ocean Forecasting Services During the Storm Gloria (January 2020) - Marcos G. Sotillo; Baptiste Mourre; Marc Mestres; Pablo Lorente; Roland Aznar; Manuel García-León; Maria Liste; Alex Santana; Manuel Espino; Enrique Álvarez (Frontiers in Marine Science, 2021)
Storm Gloria was the 10th named storm in Europe for the 2019–2020 winter season, and it severely affected Spain and France. This powerful storm represents an excellent study case to analyze the capabilities of the different ocean model systems available in the Spanish Mediterranean coasts to simulate extreme events, as well as to assess their suitability to enhance preparedness in maritime disasters with high impacts on coastal areas. Five different operational ocean forecasting services able to predict the storm-induced ocean circulation are evaluated. Three of the systems are delivered by the Copernicus Marine Service (hereafter CMEMS): the CMEMS global scale solution (GLO-1/12°), the specific Mediterranean basin scale one (MED-1/24°), and the regional solution for the Atlantic façade (IBI-1/36°), which includes also part of the western Mediterranean. These CMEMS core products are complemented with two higher resolution models focused on more limited areas, which provide operational forecasts for coastal applications: the WMOP system developed at the Balearic Islands Coastal Observing and Forecasting System (SOCIB) with a horizontal resolution of roughly 2 km and the Puertos del Estado (PdE) SAMOA systems with a 350-m resolution that cover the coastal domains of the Spanish Port Authorities of Barcelona, Tarragona, Castellón and Almeria. Both the WMOP and SAMOA models are nested in CMEMS regional systems (MED and IBI, respectively) and constitute good examples of coastal-scale-oriented CMEMS downstream services. The skill of these five ocean models in reproducing the surface dynamics in the area during Gloria is evaluated using met-ocean in situ measurements from numerous buoys (moored in coastal and open waters) and coastal meteorological stations as a reference to track the effects of the storm in essential ocean variables such as surface current, water temperature, and salinity throughout January 2020. Furthermore, modeled surface dynamics are validated against hourly surface current fields from the two high-frequency radar systems available in the zone (the SOCIB HF-Radar system covering the eastern part of the Ibiza Channel and the PdE one at Tarragona, which covers the Ebro Delta, one of the coastal areas most impacted by Gloria). The results assess the performance of the dynamical downscaling at two different levels: first, within the own CMEMS service (with their regional products, as enhanced solutions with respect to the global one) and second in the coastal down-streaming service side (with very high-resolution models reaching coastal scales). This multi-model study case focused on Storm Gloria has allowed to identify some strengths and limitations of the systems currently in operations, and it can help outlining future model service upgrades aimed at better forecasting extreme coastal events.

On the Performance of High Frequency Radar in the Western Mediterranean During the Record-Breaking Storm Gloria - Pablo Lorente; Jue Lin-Ye; Manuel García-León; Emma Reyes; Maria Fernandes; Marcos Garcia Sotillo; Manuel Espino; Maria Isabel Ruiz; Vicente Gracia; Susana Perez; Roland Aznar; Andres Alonso-Martirena; et al. (Frontiers in Marine Science, 2021)
Storm Gloria (January 19–24, 2020) hit the NW Mediterranean Sea with heavy rainfall, strong easterly winds, and very high waves, causing structural damages and 13 fatalities. The low-lying Ebro Delta (ED) region was severely inundated, ruining rice fields and seaside promenades. A variety of Copernicus Marine Environment Monitoring Service (CMEMS) modeling and observational products were jointly used to examine the fingerprint of Gloria and the response of the upper oceanic layer. According to the results, Gloria can be interpreted as a high-impact once-in-a-decade metocean event where various historical records were beaten. The 99th percentile of several parameters (wind speed, significant wave height, wave period, and surface current velocity), derived from long-term observational time series, was persistently exceeded. The atmospheric surge, albeit not negligible, exerted a secondary role in ED. The ability of a high-frequency radar deployed in this region (HFR-ED) to characterize the striking features of the storm was quantified from both waves and circulation aspects. Consistent radar current observations were subsequently compared against the 5-day-ahead forecast of CMEMS Iberia-Biscay-Ireland (IBI) regional ocean model to determine, from an Eulerian perspective, the strengths and shortcomings in its predictive capabilities. Time-averaged maps of surface circulation, superimposed with fields of Instantaneous Rate of Separation (IROS), were derived to resolve flow features and identify areas of elevated particles dispersion, respectively. The mean and P99 values of IROS almost doubled the historical statistics in the vicinity of the northern Ebro hemidelta. Although IBI predicted moderately well basic features of the storm-induced circulation, results suggests that coastal transport processes, likely modulated by wave-current interactions, were not fully captured. Furthermore, current estimations from other two radar systems, overlooking immediate choke points like the Ibiza Channel and the Strait of Gibraltar, evidenced Gloria’s remote-effect in the anomalous circulation patterns observed, that altered the usual water exchanges between adjacent sub-basins. Finally, three-dimensional outcomes from IBI were used to elucidate the impact of this moving storm at different depth levels. Data analyses illustrated that Gloria caused a large increase in kinetic energy and a significant deepening of the mixed layer depth.

Skill assessment of global, regional, and coastal circulation forecast models: evaluating the benefits of dynamical downscaling in IBI (Iberia–Biscay–Ireland) surface waters - Pablo Lorente; Marcos García-Sotillo; Arancha Amo-Baladrón; Roland Aznar; Bruno Levier; José C. Sánchez-Garrido; Simone Sammartino; Álvaro de Pascual-Collar; Guillaume Reffray; Cristina Toledano; Enrique Álvarez-Fanjul (Ocean Science, 2019)
In this work, a multi-parameter inter-comparison of diverse ocean forecast models was conducted at the sea surface ranging from global to local scales in a two-phase stepwise strategy. Firstly, a comparison of CMEMS GLOBAL and the nested CMEMS IBI regional system was performed against satellite-derived and in situ observations. Results highlighted the overall benefits of both the GLOBAL direct data assimilation in open water and the increased horizontal resolution of IBI in coastal areas. Besides, IBI (Iberia–Biscay–Ireland) proved to capture shelf dynamics by better representing the horizontal extent and strength of a river freshwater plume, according to the results derived from the validation against in situ observations from a buoy moored in NW Spain. Secondly, a multi-model inter-comparison exercise for 2017 was performed in the Strait of Gibraltar among GLOBAL, IBI, and SAMPA (Sánchez-Garrido et al., 2013) high-resolution coastal forecast systems (partially nested to IBI) in order to elucidate the accuracy of each system to characterize the Atlantic Jet (AJ) inflow dynamics. A quantitative validation against hourly currents from high-frequency radar (HFR) highlighted both the steady improvement in AJ representation in terms of speed and direction when zooming from global to coastal scales through a multi-nesting model approach and also the relevance of a variety of factors at local scale such as a refined horizontal resolution, a tailored bathymetry, and a higher spatio-temporal resolution of the atmospheric forcing. The ability of each model to reproduce a 2 d quasi-permanent full reversal of the AJ surface inflow was examined in terms of wind-induced circulation patterns. SAMPA appeared to better reproduce the reversal events detected with HFR estimations, demonstrating the added value of imposing accurate meteorologically driven barotropic velocities in the open boundaries (imported from the NIVMAR (Álvarez-Fanjul et al., 2001) storm surge model) to take into account the remote effect of the atmospheric forcing over the entire Mediterranean basin, which was only partially included in IBI and GLOBAL systems. Finally, SAMPA coastal model outputs were also qualitatively analysed in the western Alboran Sea to put in a broader perspective the context of the onset, development, and end of such flow reversal episodes.

Regional circulation patterns of Mediterranean Outflow Water near the Iberian and African continental slopes - Álvaro de Pascual-Collar; Marcos G. Sotillo; Bruno Levier; Roland Aznar; Pablo Lorente; Arancha Amo-Baladrón; Enrique Álvarez-Fanjul (Ocean Science, 2019)
The Mediterranean Outflow Water (MOW) is a dense water mass originated in the Strait of Gibraltar. Downstream of the Gulf of Cádiz, the MOW forms a reservoir region west of the Iberian continental slopes at a buoyant depth of approximately 1000 m. This region plays a key role as the main centre where the MOW is mixed and distributed into the North Atlantic. The seafloor in this area is characterized by the presence of a complex bathymetry with three abyssal plains separated by mountain chains. Although the topographic features do not reach the surface, they influence ocean flows at intermediate and deep ocean layers, conditioning the distribution and circulation of MOW. The Copernicus Marine Environmental Monitoring Service (CMEMS) Iberian–Biscay–Ireland (IBI) ocean reanalysis is used to provide a detailed view of the circulation and mixing processes of MOW near the Iberian and African continental slopes. This work emphasizes the relevance of the complex bathymetric features defining the circulation processes of MOW in this region. The high resolution of the IBI reanalysis allows us to make a description of the mesoscale features forced by the topography. The temperature, salinity, velocity, transport, and vorticity fields are analysed to understand the circulation patterns of MOW. The high-resolution circulation patterns reveal that Horseshoe Basin and the continental slope near Cape Ghir (a.k.a. Cap Rhir or Cabo de Aguer) are key areas controlling the mixing processes of MOW with the surrounding water masses, mainly North Atlantic Central Water (NACW) and Antarctic Intermediate Water (AAIW). The water mass variability is also analysed by means of composite analysis. Results indicate the existence of a variability in the MOW tongue which retracts and expands westwards in opposition to the movement of the underlying North Atlantic Deep Water.

Mediterranean Sea response to climate change in an ensemble of twenty first century scenarios - Fanny Adloff; Samuel Somot; Florence Sevault; Gabriel Jordà; Roland Aznar; Michel Déqué; Marine Herrmann; Marta Marcos; Clotilde Dubois; Elena Padorno; Enrique Alvarez-Fanjul; Damià Gomis (Climate Dynamics, 2015)

FishMed: traits, phylogeny, current and projected species distribution of Mediterranean fishes, and environmental data - Camille Albouy; Frida Ben Rais Lasram; Laure Velez; François Guilhaumon; Christine N. Meynard; Séverine Boyer; Laura Benestan; Nicolas Mouquet; Emmanuel Douzery; Roland Aznar; Marc Troussellier; Samuel Somot; et al. (Ecology, 2015)
The FishMed database provides traits, phylogeny, current and projected species distribution of Mediterranean fishes, and associated sea surface temperature (SST) from the regional oceanic model NEMOMED8. Data for the current geographical distributions of 635 Mediterranean fish species were compiled from a published expert knowledge atlas of fishes of the northern Atlantic and the Mediterranean (FNAM) edited between 1984 and 1986 and from an updated exotic fish species list. Two future sets of projected species distributions were obtained for the middle and end of the 21st century by using an ensemble forecasting approach for 288 coastal Mediterranean fish species based on SST according to the IPPC/SRES A2 scenario implemented with the Mediterranean climatic model NEMOMED8. The functional part of the database encompasses 12 biological and ecological traits (maximal and common lengths, vertical distribution, habitat, migration type, mode of reproduction, sex shift, semelparity, diet type (larvae and adults), social behavior, species origin, and depth) for the 635 fish species. To build the phylogeny we inferred the timing and geographic origins of Mediterranean teleost species diversity using nucleotide sequences collected from GenBank including 62% of Mediterranean teleost species plus nine outgroups. Maximum likelihood Bayesian phylogenetic and dating analyses were calibrated using 20 fossil species. An additional 124 fish species were grafted onto the chronogram according to their taxonomic affinity to obtain a phylogenetic tree including 498 species. Finally we also present the associated SST data for the observed period (1961–1980) and for the middle (2040–2059) and the end of the 21st century (2080–2099) obtained from NEMOMED8 according to the IPCC A2 scenario. The FishMed database might be of interest in the context of global anthropogenic changes as coastal Mediterranean ecosystems are currently recognized as one of the most impacted ecosystems on earth.

Projected climate change and the changing biogeography of coastal Mediterranean fishes - Camille Albouy; François Guilhaumon; Fabien Leprieur; Frida Ben Rais Lasram; Samuel Somot; Roland Aznar; Laure Velez; François Le Loc'h; David Mouillot (Journal of Biogeography, 2013)
Aim To forecast the potential effects of climate change in the Mediterranean Sea on the species richness and mean body size of coastal fish assemblages. Location The Mediterranean Sea. Methods Using an ensemble forecasting approach, we used species distribution modelling to project the potential distribution of 288 coastal fish species by the middle and end of the 21st century based on the IPCC A2 scenario implemented with the Mediterranean climatic model NEMOMED 8. Results A mean rise of 1.4 °C was projected for the Mediterranean Sea by the middle of the 21st century and 2.8 °C by the end of the 21st century. Projections for the end of the century suggest that: (1) 54 species are expected to lose their climatically suitable habitat, (2) species richness was predicted to decrease across 70.4% of the continental shelf area, especially in the western Mediterranean Sea and several parts of the Aegean Sea, and (3) mean fish body size would increase over 74.8% of the continental shelf area. Small‐bodied species that are not targeted by either commercial or recreational fleets presented, on average, the highest predicted decrease in geographic range size. Main conclusions Projected climate change in the Mediterranean Sea may have deleterious effects on coastal fish diversity, including a significant loss of climatically suitable habitat for endemic fish species. In addition, climate change may contribute to the loss of small and low trophic‐level fishes, which may have ecosystem‐wide impacts by reducing food supply to larger and higher trophic‐level species. Fishing pressure is already selectively removing large‐bodied species from marine ecosystems, and so fishing and climatic change might act in tandem to drive both direct and secondary extinctions.